Analysis of health indicators in patients with diabetes treated at Hiperdia Center of Viçosa - de Lade, Carlos Gabriel; Bouzas Marins, João Carlos; Moreira Lima, Luciana; Sepúlveda Reis, Janice; Teixeira Reis, Hamilton Henrique; Tolêdo Caetano, Isabella; dos Santos Amorim, Paulo Roberto (O Mundo da Saúde, 2016)
The prevalence of diabetes mellitus is being considered a global epidemic, with 382 million people currently affected worldwide and increase forecast for 592 million for the year 2035. Currently, Brazil is the fourth country in the world in number of diabetes. This study aimed to describe the epidemiological characteristics of individuals with diabetes mellitus treated at Hiperdia Center of Viçosa-MG, considering socio demographic, modifiable risk factors and not modifiable. This is a descriptive study, quantitative, documentary and cross-sectional. 547 records were analyzed, 218 retirees and 329 active patients. The analysis of the active patients showed that 51% of the total number of patients had a higher prevalence of type 2 diabetes mellitus associated with hypertension. In relation to active patients, 72% had low family income, 74% had low education, 74%, 78 % and 57% had high prevalence of hypertension, overweight/obesity, physical inactivity, respectively. The presence of two or more family history of coronary and metabolic diseases was found in 79% of patients. The analysis of fasting and postprandial proved inadequate values by more than 50% of the active patients. Patients with diabetes attended by the Hiperdia Center of Viçosapresented in addition to the disease itself, modifiable and non-modifiable risk factors, both being complicating for diabetes control and a good health.